Suspended sediment variability at the Solimões and Negro confluence between May 2013 and February 2014 - Marinho, Thiago (2018)
This study focuses on the confluence of two major rivers of the world, the Solimões River (white waters) and Negro River (black waters). Surface suspended sediment samples (SSC) and spectroradiometer taken along transverse profiles at 500 m intervals over a distance of 10 km, as well as satellite images (MODIS) during the hydrological year, were used to follow suspended sediment variability. In January and February, the confluence is dominated by white waters from the Solimões River in the two banks, and in June and July in the right bank by black waters from the Negro River and in the left bank by clear waters from the Solimões River. We found that indirect tools, such as reflectance obtained by spectrometer or MODIS images, can be used to determine surface suspended sediments in a contrasting zone.